Generalized structure map of top, middle, and basal tertiary markers with geothermal gradients, eastern north slope petroleum province, Alaska - Tailleur, I.L.; Engwicht, S.E. (comps.) (Geological Survey, Reston, VA (USA), 1978)
This map shows structure contours on several markers in the Tertiary rocks in the Prudhoe Bay area and the regional geothermal gradients. Contours of the geothermal gradient (Am. Assoc. Petroleum Geologists, undated) apparently correlate with other geologic trends. The lower gradients coincide with the deepest part of the Colville basin, and the higher gradients with the thinner section of sediments deposited over the Barrow arch. The inflection of the isograds in the vicinity of Prudhoe Bay may be due to an insulating effect from the hydrocarbon accumulation and(or) a slightly greater proportion of poorly conductive rocks. Heat flow in the area of Prudhoe Bay is essentially the same as other regions in the Arctic (Gold and Lachenbruch, 1973).